DAYA TARIK QUEEN STAR WATERPARK DI KABUPATEN SIAK - Elana Apriani; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Queen Star Waterpark Siak is the only water playground in Siak Regency. This Queen Star Waterpark has several attractions, visitors can swim, play, and relax enjoying a pleasant experience while on this object. To measure what the appeal of Queen Star Waterpark has met the standard of attraction at a tourist destination, and this is measured from 3 components, namely: Something To See (something to see), Something To Do (something to do), and Something To Buy (something to buy). This research will be measured and known by quantitative methods with data collection techniques of observation,interviews, documentation and questionnaires. Samples or respondents taken as many as 100 respondents. Based on the research that has been done, it shows that the characteristics of visitors are mostly women, at the age characteristics of 21-30 years, most of them are students or students and come from local visitors. The results of processed data carried out resulted in a tourist attraction score in the excellent category with a score range of 2998.  Keywords: attractiveness, visitors